A novel electrophoretic immunoblot as antigen desorption and quantification method for alum-adjuvanted veterinary rabies vaccines. Issue 27 (2nd June 2020) - Morgenroth, Anna; Jakel, Verena; Hanke-Robinson, Heidrun; Müller, Thomas; Freuling, Conrad; Cussler, Klaus; Duchow, Karin; Krämer, Beate; Bastian, Max
Abstract: Rabies vaccines for domestic animals are adjuvanted with aluminum salts. A particular challenge for in-vitro batch potency tests with these products is the fact that the antigens are firmly adsorbed to the aluminum salt matrix and thus are not easily available for antigen quantification. In the current manuscript we describe a versatile technique to quantify antigens in aluminum adsorbed vaccine formulations. A combined electrophoretic desorption and blotting method is presented that transfers the antigens to a nitrocellulose membrane followed by an immunoblot quantification of the transferred rabies antigens. For the immunoblot a rabies G-protein specific, monoclonal antibody is used that by itself has neutralizing activity. This ensures that only relevant antigens are quantified. By comparing end products with non-adjuvanted in-process material it can be demonstrated that the antigens are quantitatively desorbed from the adjuvant matrix. Resuts of the new antigen quantification method were compared with the outcome of the serological batch potency test as described in the European Pharmacopoeia. It is demonstrated that the new antigen quantification method reveals relevant differences between experimental vaccine batches formulated with increasing antigen loads. This proves the broad detection range of the method. In general, the results show that this highly versatile technique can serve as an important component of a comprehensive consistency test strategy and may be applied in a modified form to any alum-adjuvanted vaccine.